PENGARUH E - SERVICE QUALITY TERHADAP KEPUASAN PELANGGAN PENGGUNA APLIKASI EMOS (ENSEVAL MOBILE ORDER SYSTEM) PADA PT. ENSEVAL PUTERA MEGATRADING, TBK CABANG SAMARINDA - Titik Yuliana; Eddy Soegiarto; Adisty Shabrina Nurqamarani (RJABM (Research Journal of Accounting and Business Management), 2019)
This study aims to determine the effect of E-Service Quality which includes Efficiency, Reliability, Fullfilment, Privacy, Responsiveness and Contact on Customer Satisfaction on users of the EMOS Application (Enseval Mobile Order System). The basic theory used in this research is Marketing Management, E-Service Quality and Customer Satisfaction. The population in this study was 266 pharmacies and samples taken were 73 pharmacies with simple random sampling technique. Data collection was done by distributing online questionnaires using a Likert scale to measure each indicator of the independent and dependent variable. The analytical tool used is multiple linear regression.The results of the research on the f test show that the E-Service Quality variables which include Efficiency, Reliability, Fullfilment, Privacy, Responsiveness and Contact have a significant effect simultaneously (simultaneously) on Customer Satisfaction. The t test shows that the independent variables; reliability and contact affect customer satisfaction while the variables Efficiency, Fullfilment, Privacy and Responsiveness do not affect the customer satisfaction of users of the EMOS application (Enseval Mobile Order System).